Pengaruh Peran Orang Tua Terhadap Motivasi dan Lingkungan Belajar Siswa di MAN 2 Mojokerto - Isyroq Ziyaul Haq Adaniyah; Jani Jani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study is interested in uncovering the extent to which parental roles, such as emotional support, involvement in learning activities, and provision of learning facilities, can influence students' intrinsic and extrinsic motivation, as well as creating a conducive learning environment at home. By taking MAN 2 Mojokerto as the object of research, it is hoped that the results of this study can provide a clearer picture of the dynamics of interaction between family and school in shaping student character and achievement.The formulation of the problem obtained by the author is how the influence of the role of parents on student learning motivation at MAN 2 Mojokerto, and how the influence of the role of parents on the student learning environment at MAN 2 Mojokerto. From the formulation of the problem, the author's goal is to determine the effect of the role of parents on the motivation and learning environment of students.The results showed: significantly there is a positive and significant relationship between the role of parents on student motivation and learning environment, and significantly there is an influence between the role of parents on student motivation and learning environment. This is evidenced by the results of simple regression analysis based on the simple regression test results showing a value of 0.001. Based on the decision-making guidelines if the significance value is <0.05, it means that variable X has an effect on variable Y. The conclusion is 0.001> 0.05, which means that variable X has a significant effect on variable Y. Based on the hypothesis, H1 is accepted and H0 is rejected.